Purchasing Decision Behaviours of Health Insurance Products and The Determinants of Competitive Advantage - Sudirjo, Frans; Sulistiyani, Sulistiyani (Indonesian Journal of Business and Entrepreneurship, 2023)
As a company that provides services in managing risks, coverage for the uncertainties faced by potential customers in the future makes the insurance business utilize several marketing models, such as personal selling combined with competitive premium prices and service quality. This study aimed to analyze the effect of competitive price strategies, service quality, and personal selling on purchasing decisions for health insurance products in Indonesia by implementing the role of mediating competitive advantage. This research was conducted using a random sampling technique using a sample of 220 respondents from customers of health insurance products in Greater Semarang, Central Java, Indonesia. Data was collected by distributing questionnaires, which were processed and analyzed using PLS (Partial Least Square) with SEM Structural Equation Modeling (SEM) with WarpPLS software. The results of the study show that personal selling, competitive price strategies and service quality positively affect competitive advantage and purchasing decisions. The findings also confirm the mediating role of competitive advantage in bridging the relationship between independent variables and purchasing decisions. Practically, these findings underscore the importance of health insurance uniqueness as an important part of the formation of purchasing decisions by custumers. Keywords: personal selling, competitive price, service quality, competitive advantage, purchasing decision